Storage of Cocoa (Theobroma Cacao L.) Seeds and Changes Associated With Their Deterioration - Hor, Yue Luan (1984)
Cocoa (Theobroma cacao L .) seeds are recalcitrant and rapidly lose their viability during preparation and within two to three weeks of storage. To improve their storability, the responses of a cultivar of cocoa seeds (NA 33) to different drying methods and storage factors including seed moisture, storage temperature and fungi were investigated. Physiological, biochemical and structural changes associated with seed death caused by dehydration in the air-conditioned room (22oC, 55% RH) and chilling at 100C were also monitored.